Nauka stoicka Seneki i jej koegzystencja z wartościami chrześcijańskimi we fragmencie „Żywota człowieka poczciwego (Cnota – wielka królowa)” Mikołaja Reja. Retoryka na usługach dydaktyki: Seneca’s stoical education and its co-existence with christian values in the fragment of „Żywot człowieka poczciwego (Cnota – wielka królowa)” by Mikołaj Rej. Rhetoric on didactic services - Ejzak, Bartosz (Prace Polonistyczne, 2019)
The author utilizes a fragment of the Żywot człowieka poczciwego (Cnota – wielka królowa) by Mikołaj Rej, to prove that the Polish author reinterpreted Seneca’s ideas and adapted them to be in harmony with Christian teaching. The author invokes, above all, the authority of Lucius Lipsius. By comparing particular fragments of Rej’s work to Myśli and Moral letters to Lucilius by Seneca he shows numerous similarities between the philosophical systems of these two authors. For example, finds correspondence in their attitudes to virtue, material goods, prudence, fame and truth. However, there are also differences, including Rej’s and Seneca’s opinion on suicide. Finally, the author analyzes the stylistic devices that enabled Rej to create a guide that promotes neo-stoic values.